KEBIJAKAN BERWAWASAN KEPENDUDUKAN BERBASIS KARAKTER SUMBER DAYA MANUSIA BERKUALITAS - Deny Setiawan (Universitas Negeri Medan, 2016)
Population problems which are increasingly widespread and threaten the sustainability of the planet, requires serious treatment from state institutions such as the presence of policies pertaining to the population. People-oriented policy center, formulated in order to build human resources are aware of the importance of the preservation of the earth through the appearance character is qualified through the ownership of the life skills, personal skills, self awareness and thinking skills, social skills, academic skills, vocational skills adan. With the provision of life skills, is expected to be born human character knowledgeable, thinker, a risk-taker, caring, reflective Inquirer and who have a commitment to act in solving and addressing population issues.Kata Kunci: Wawasan Kependudukan, Sumber Daya Manusia, Karakter